2019
DOI: 10.33557/binabahasa.v12i2.741
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Collaborative Technique in Teaching Writing to Enhance Students’ Skill in Writing English Text

Abstract: This study aims to seek insight into the use of Collaborative techniques in enhancing students’ interest in writing English and analyzing students' character development in writing skills by applying Collaborative techniques. It employs qualitative descriptive research where the primary data analyzed is the development of students’ writing interest and skill during the time of the implementation of the Collaborative Technique. In addition, as secondary data, the analyses of interview and classroom observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
2
1
0
Order By: Relevance
“…Students felt more passionate about writing because they write with their peers. This finding is in line with research by Inayah (2019), whose research found that students' motivation in writing English is increased by using the collaborative approach, which also helps them improve their own writing abilities.…”
Section: Motivationsupporting
confidence: 91%
“…Students felt more passionate about writing because they write with their peers. This finding is in line with research by Inayah (2019), whose research found that students' motivation in writing English is increased by using the collaborative approach, which also helps them improve their own writing abilities.…”
Section: Motivationsupporting
confidence: 91%
“…The overall findings align with the previous studies on the benefits of collaborative writing in enhancing students' language skills other elements, including Grammar and vocabulary (Guo et al, 2021;Inayah, 2019;Storch, 2019).…”
Section: Affordances For Language Skills and Aspects Developmentsupporting
confidence: 90%
“…Trimbur in Lassiter ( 2014) the purpose of collaborative learning is to initiate in-depth conversations between pairs or small groups, then between groups in the class, and then between the class and the teacher. In addition, Ratih Inayah (2019) says that, the collaborative writing process is proven to help teachers empower students' writing skills and develop students' abilities to work with others so as to reduce selfish behavior.…”
Section: Student's Perception About Collaborative Writingmentioning
confidence: 99%